ESTUDIOS SOBRE LA MICROBIOLOGIA DEL PULQUE III ACTIVIDAD DEXTRANOGENICA DE LEUCONOSTOC AISLADOS DEL AGUAMIEL - SANCHEZ MARROQUIN, AY; ARCINIEGA, L (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1948)
5 strains of Lactobacillus sp isolated from pulque, probably belonging to a sp n still under study, were used in the lactic fermentation of hydrolyzed aguamiel ( a non-fermented juice from a sp of Agave) Strain II showed higher yields than I delbru
AN ESC NAC CIENC BIOL
Keywords: ESTUDIOS, MICROBIOLOGIA, PULQUE, ACTIVIDAD DEXTRANOGENICA, LEUCONOSTOC, AGUAMIEL; CIENCIAS DE LA VIDA; MICROBIOLOGIA; PROCESOS MICROBIANOS